[en] JOSÉ MARTÍ AND THE UNITED STATES: THE HISTORICAL INTERPRETATION OF AMERICAN SOCIETY IN THE CHRONICLES OF THE CUBAN INTELLECTUAL JOSÉ MARTÍ (1853-1895) - LUCAS MACHADO DOS SANTOS (MAXWELL, 2018)
[pt] A presente tese propõe a análise da produção intelectual do cubano José Martí, com foco em seus estudos sobre a sociedade norte-americana do século XIX, observada durante o período de mais de uma década (1880-1895). As fontes que formam o cerne do objeto de investigação são o conjunto de crônicas publicadas em diferentes periódicos da América Hispânica, comumente chamados de Escenas Norteamericanas. A investigação da base filosófica que constituiu a visão de mundo do autor; sua interpretação acerca do significado da modernidade, a realização do exercício de perspectiva, propiciado pela experiência do exílio; o diálogo com as correntes históricas do pensamento social norte-americano, sobretudo o abolicionismo, o pensamento reformador, o debate da forma da vida religiosa em interação com a vida política, o anarquismo e o socialismo, nos permite valorizar a compreensão da história dos Estados Unidos por ele investigada, de um modo que destacou a importância da análise da vida espiritual para uma consideração correta da história e da cultura desta sociedade. Desse modo, a literatura, a filosofia, o pensamento social e político foram os elementos essenciais e indissociáveis de seu exercício de interpretação histórica. === [en] The present thesis proposes the analysis of the intellectual production of the Cuban Jose Marti, focusing on his studies on the American society of the 19th century, observed during the period of more than a decade (1880-1895). The sources that form the core of the object of investigation are the set of chronicles published in different periodicals of Hispanic America, commonly called Escenas Norteamericanas. The investigation of the philosophical basis that constituted the world view of the author; his interpretation of the meaning of modernity, the realization of the exercise of perspective, propitiated by the experience of exile; the dialogue with the historical currents of American social thought, especially abolitionism, reformist thought, the debate of the form of religious life in interaction with political life, anarchism and socialism, allows us to value the understanding of the history of the United States by him investigated, in a way that emphasized the importance of the analysis of spiritual life for a correct consideration of the history and culture of this society. In this way, literature, philosophy, social and political thought were the essential and inseparable elements of his exercise of historical interpretation.